Urothelial Carcinoma of the Bladder in Patients on Hemodialysis: Clinical Characteristics and Oncological Outcomes - Yossepowitch, Ofer; Sagy, Itay; Margel, David; Baniel, Jack (The Journal of urology, 2012)
Purpose We characterized the clinical presentation and outcome of patients on hemodialysis diagnosed with urothelial carcinoma of the bladder. Materials and Methods Patients treated for bladder cancer while undergoing maintenance hemodialysis were identified by querying the medical registry of a university affiliated hospital between 1999 and 2010. Clinical, pathological and treatment related data were retrieved and characterized. The study end points were recurrence-free, progression-free and overall survival. Results A total of 15 patients met study criteria. Median age at hemodialysis onset was 67 years (IQR 62, 74). Median dialysis duration before the bladder cancer diagnosis was 36 months (IQR 12, 60). Hematuria and bloody urethral discharge were the most common clinical manifestations. Tumors were generally large and multifocal. Of the patients 66% had invasive disease (T1 or greater) at presentation and 73% had high grade tumors. There were no adverse sequelae after transurethral resection or intravesical therapy. Two of the 4 patients treated with total urinary exenteration died soon after surgery and 1 had a grade IV complication. At a median followup of 18 months the estimated recurrence-free survival rate was 54% at 1 year, and 43% each at 2 and 3 years. The progression-free survival rate was 78%, 56% and 42%, and the overall survival rate was 66%, 45% and 23% at 1 to 3 years, respectively. Conclusions Bladder cancer diagnosed in patients on hemodialysis often harbors aggressive histological features at presentation. Conservative therapy in patients with noninvasive tumors appears to be well tolerated while urinary tract exenteration is associated with high morbidity and mortality. The prognosis of patients with invasive cancer is generally dismal.